RFID-based cashless payment system / Mohammad Farid Saaid and Muhammad Naim Handani - Saaid, Mohammad Farid; Handani, Muhammad Naim (UiTM Press, 2014)
Nowadays, most of the supermarkets or retail organizations use the old-fashioned or conventional data management and payment system. This current technology would affect the productivity and face the consequences of this lacking technology. Thus, some weaknesses such as data losses, longer waiting time and many more will get involved in this matter. Therefore, it is very crucial to propose a new intelligent system with real-time and overcomes the limitations of the conventional management system. Radio Frequency Identification (RFID) technology is the most leading and suitable to be proposed to overcome this limitation because it is wireless technology, which using radio frequency as its method of data transmission. Other than that, the Barcode technology will be used as the way of tracking the product since a barcode system is the cheapest way, and it has still been using widely in a retail management system. Based on the study conducted, an RFIDbased Cash less invented to help the customer to make payment without involving any cash but using RFID tag that contains electronically cash yet it can increase the smoothness while making payment. This system is developed with Graphical User Interface (GUI) as user interfaces on the monitor to print out and present the retrieved data information from a database that developed with Microsoft Access, buzzer as the sound indicator to show that the tag already scanned and green and red LED as the light indicator to show the products are ready to be scanned. During the development stage, the hardware, middleware and programming integrated together for a complete system. After that, some experimental test is conducted on investigate the system capabilities such as detection capabilities towards materials and the effect of tag position on tag detection distance. In a nutshell, this cash fewer payment systems helped the customers to make payment in a shorter period instead of the conventional method.